2022
DOI: 10.2147/nrr.s338161
|View full text |Cite
|
Sign up to set email alerts
|

The Preterm Birth Rate in a Resource-Stricken Rural Area of the Limpopo Province, South Africa

Abstract: Background: Midwives play a pivotal role in providing primary prevention of preterm birth. Midwives screen and diagnose preexisting medical conditions, manage all conditions as guided by their scope of practice and refer all cases to other relevant team members. Purpose:The study aimed to determine and describe factors contributing to the escalating preterm birth rate in Limpopo, South Africa. Methods: Descriptive survey was used to determine factors related to increased preterm births. The non-probability pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Access to health services and the presence of health workers who can help mothers must also be considered [ 25 27 ]. A study conducted by Malwela et al [ 28 ], in rural areas in South Africa, shows that the cause of the increasing incidence of preterm births is the availability of equipment, which is less than 40%, making preterm births unpreventable. This is also related to research by Pervin et al, in which pregnant women rarely had ANC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to health services and the presence of health workers who can help mothers must also be considered [ 25 27 ]. A study conducted by Malwela et al [ 28 ], in rural areas in South Africa, shows that the cause of the increasing incidence of preterm births is the availability of equipment, which is less than 40%, making preterm births unpreventable. This is also related to research by Pervin et al, in which pregnant women rarely had ANC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with research by Li et al, whose results showed weak differences in the risk of preterm birth among five urban-rural types [ 27 ]. In addition, ANC screening also has a positive influence in detecting some pregnancy complications, and this can trigger the offer of perinatal treatment to improve outcomes and prognosis for prematurity [ 28 ]. In accordance with research conducted by Beeckman et al shows that women without antenatal care are at higher risk for preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many religions classify homosexual behavior, sex work, and drug use as immoral, which are behaviors often associated with HIV and mental health. As a result, church members may promote HIV and mental health stigma through moralistic attitudes and conservative ideologies (Malwela, 2019;Campbell et al, 2011). In many BSSA communities, religious leaders are seen as powerful gatekeepers who control what happens within their communities (Nyashanu & Serrant, 2016).…”
Section: Religionmentioning
confidence: 99%
“…Despite the recognition of the importance of parental involvement in NICU care and the documented emotional challenges experienced by parents, there is a gap in the literature regarding the specific experiences and cultural practices of parents caring for preterm infants which can be integrated in NICU in settings, such as Limpopo Province in South Africa. The province has seen a significant increase in the number of newborn babies weighing under 2,500 grams in recent years [ 19 ]. The study aimed to explore and describe the cultural determinants of parents that can be integrated into the care of preterm infants admitted to the NICU in Limpopo Province to ensure culturally sensitive care.…”
Section: Introductionmentioning
confidence: 99%